A Decision Support System for Multiple Team Formation - Cunha, Felipe; Perkusich, Mirko; Almeida, Hyggo; Perkusich, Angelo; Gorgônio, Kyller (Anais do Workshop Brasileiro de Engenharia de Software Inteligente (ISE); 2021: Anais do I Workshop Brasileiro de Engenharia de Software Inteligente, 2021)
This work presents a Decision Support System to assist multiple team formation in the context of software development. After analysis of recent works in the literature, it was found that the approaches are still unable to reflect the real needs of the industry, which makes their practical application difficult. Our findings confirm the benefits of our prototype developed to researchers who are interested in comprehending the team formation problem and industry practitioners who may be interested in understanding how Decision Support Systems can support the teams formation.